Design and analysis of unmanned surface vehicle for phytoplankton detection - Muhammad Hisyam, Azman (2016)
Phytoplankton is the heart of marine ecosystem. It is the basic aquatic food webs and acts as the food provider to marine organisms. Phytoplankton is like normal plant, requires sunlight to perform photosynthesis. It consumes carbon dioxide, releases oxygen and contains chlorophyll. The presence of phytoplankton is essential to form a balance ecosystem. However the phytoplankton can also bring harm. When there is too many nutrients available, phytoplankton may bloom out of control. Uncontrolled phytoplankton blooms can form harmful algal blooms (HABs) and can disturb a balanced marine ecosystem. In conjunction to that, making phytoplankton detection is the first and important step to prevent the harmful algal blooms. The aim of this research project is to develop an instrument that can simplify the way of phytoplankton detection. The main goal of this project is to design and analysis a comprehensive design methodology, implementation and testing of an instrument to be embedded to an unmanned surface vehicle.